Activated Carbon from Mangrove Wood (Rizophora apiculata): Preparation and Characterization - Ahmad Zulkarnain, Zuriati; Hussien, Mohd Zobir; Badri, M. (1992)
Activated carbon was prepared from mangrove wood (Rizophora apiculata) by destructive distillation in vacuum. A series of heating times and temperatures were selected for the preparation of activated carbon. The iodine number of the activated carbon was determined by absorption method in aqueous solution. The plot of iodine number as a function of heating temperature revealed that the maximum iodine number was attained at 500·C after heating for 3 hours. Determination of trace elements, pore sizes and surface topography was also carried out.